2010
DOI: 10.1037/a0018753
|View full text |Cite
|
Sign up to set email alerts
|

Development, refinement, and psychometric properties of the Attitudes Toward God Scale (ATGS-9).

Abstract: Perceived relationships with God can be a source of comfort or struggle. To advance the study of spiritual comfort and struggle, we develop the nine-item Attitudes toward God Scale (ATGS-9), and we describe six studies (2,992 total participants) reporting its development and psychometrics. Exploratory and confirmatory factor analyses identified two factors: (1) Positive Attitudes toward God and (2) Disappointment and Anger with God. Subscale scores showed good estimated internal consistency, 2-week temporal st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
152
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(170 citation statements)
references
References 68 publications
(87 reference statements)
14
152
0
4
Order By: Relevance
“…The questionnaire includes, besides demographics and space for free-text entries of respondents' definitions of religion and spirituality, Hood's (1975) Mysticism Scale, the Big Five (NEO-FFI, Costa & McCrae, 1985), Granqvist's (2002) Attachment Items, Exline's Attitudes toward God Scale (Wood, Worthington, Exline, Yali, Aten, & McMinn, 2009), Ryff's Psychological Well-Being and Growth Scale (Ryff 1989;Ryff & Singer, 1998), the Loyola Generativity Scale (McAdams & de St. Aubin, 1992), and the Religious Schema Scale (Streib, Hood, & Klein, 2010). These measures allow further profiling of self-identifications and their correlates.…”
Section: Introductionmentioning
confidence: 99%
“…The questionnaire includes, besides demographics and space for free-text entries of respondents' definitions of religion and spirituality, Hood's (1975) Mysticism Scale, the Big Five (NEO-FFI, Costa & McCrae, 1985), Granqvist's (2002) Attachment Items, Exline's Attitudes toward God Scale (Wood, Worthington, Exline, Yali, Aten, & McMinn, 2009), Ryff's Psychological Well-Being and Growth Scale (Ryff 1989;Ryff & Singer, 1998), the Loyola Generativity Scale (McAdams & de St. Aubin, 1992), and the Religious Schema Scale (Streib, Hood, & Klein, 2010). These measures allow further profiling of self-identifications and their correlates.…”
Section: Introductionmentioning
confidence: 99%
“…(Note, however, that restriction of age ranges in undergraduate samples limits available evidence of age differences in anger toward God.) Prior studies have not shown consistent associations with gender, ethnicity, or religiousness (Exline et al 2011;Wood et al 2010). Granted, people who are more religious are more likely to see God as the cause of events in general (e.g., Gorsuch and Smith 1983;Weeks and Lupfer 2000), including negative events (Gray and Wegner 2010;Hale-Smith et al 2012); however, they typically see God's intent as positive, which attenuates or at least dilutes angry feelings to some degree (Exline et al 2011;Wilt et al 2017).…”
Section: Key Findings On Anger Toward God From Predominantly Christiamentioning
confidence: 95%
“…Typically, those in the U.S. who believe in God report emotions about God that are much more positive than negative (Exline et al 2011;Wood et al 2010), even in contexts involving serious suffering, such as chronic pain or the terminal illness of a loved one ). Positive and negative emotions involving God usually show weak to moderate negative associations (e.g., Exline et al 2011;Wood et al 2010).…”
Section: Key Findings On Anger Toward God From Predominantly Christiamentioning
confidence: 99%
See 1 more Smart Citation
“…Religiosity using the centrality of religiosity scale, CRS-5, which contains one question on each of the centrality of religion dimensions which are scored on a frequency scale of 1 to 5 (Huber and Huber 2012). Attitude towards a deity will be measured using the ATG-S 9 (Wood et al 2010). Attachment to God, which has been commonly used and associated with disordered eating (Homan and Boyatzis 2010) and body image (Homan 2012), will be measured using the Attachment to God Scale (Rowatt and Kirkpatrick 2002) this is briefer than the Attachment to God Inventory (Beck and McDonald 2004).…”
Section: Outcome Measuresmentioning
confidence: 99%